2019
DOI: 10.1002/ccr3.2259
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose activation and reversible beige coloration in adipose tissue with multiple accumulations of 18F‐fluorodeoxyglucose in sporadic paraganglioma: A case report

Abstract: In pheochromocytoma/paraganglioma, nontumorous high 18F‐fluorodeoxyglucose accumulations are observed in both beige and brown adipose tissues. Recognizing this feature of 18F‐fluorodeoxyglucose accumulation can help physicians make precise diagnoses and help them avoid the pitfalls of a false‐positive 18F‐fluorodeoxyglucose positron emission tomography result, preventing unnecessary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In line with the reversible nature of BAT whitening in mice [39], intermittent cold exposure of adult humans increases cold‐induced BAT activity [62–64]. Given the substantial browning capacity of human adipocytes in vitro (Figs 2 and 4) and the evidence that dormant brown and brite adipocytes appear to be recruitable by thermogenic stimulation throughout the human body [42,44,65,66], achieving meaningful improvements in patient health through thermogenic activation appears to be a realistic and viable opportunity.…”
Section: The Phenotypic Versatility Of Mammalian Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…In line with the reversible nature of BAT whitening in mice [39], intermittent cold exposure of adult humans increases cold‐induced BAT activity [62–64]. Given the substantial browning capacity of human adipocytes in vitro (Figs 2 and 4) and the evidence that dormant brown and brite adipocytes appear to be recruitable by thermogenic stimulation throughout the human body [42,44,65,66], achieving meaningful improvements in patient health through thermogenic activation appears to be a realistic and viable opportunity.…”
Section: The Phenotypic Versatility Of Mammalian Adipose Tissuementioning
confidence: 99%
“…Browning of WAT in humans in vivo has been observed in different anatomical locations as a secondary effect of pathophysiological conditions (such as paraganglioma, pheochromocytoma, burn injury, and cancer-associated cachexia), but also in response to change of season and repeated localized cold exposure [42][43][44][45][46][47][48][49][50]. Brite adipocytes are, however, largely absent in the WAT of most adult humans under normal conditions, possibly due to living in thermoneutral conditions.…”
Section: Adipocyte Transdifferentiation In the Human Adipose Organmentioning
confidence: 99%
“… 18 , 19 The key similarities and differences between brown and beige adipocytes are summarised in Table 1 . It has been reported that WAT can be converted into beige adipose tissue, 8 , 20 which could represent an additional approach for treating obesity.…”
Section: Brown Adipose Tissue (Bat)mentioning
confidence: 99%